2017
DOI: 10.1016/j.jaim.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Amalaki Rasayana on telomerase activity and telomere length in human blood mononuclear cells

Abstract: BackgroundIndian traditional medicine practices use defined rasayana preparations to improve the quality of life in aged individuals. Amalaki Rasayana is one such rasayana prepared from the fruits of Phyllanthus emblica and is popularly used to prevent or treat various age related health conditions. Telomerase activity in the cells maintains telomere length and is implicated in ageing and various diseases wherein the shortening of telomere during ageing is controlled chiefly by the telomerase activity.Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…AR has also been revealed to be able to suppress neurodegeneration in fly models of Huntington's and AD [47]. A recent study with humans aged 45 to 60 years reported an increase in telomerase activity with no discernible change in telomere length in peripheral blood mononuclear cells following AR administration, suggesting that AR can avoid the telomeres erosion, promoting healthy ageing [48]. In aged human participants, AR intake maintained, or even enhanced, the DNA strand break repair, with no toxic effects [49].…”
mentioning
confidence: 99%
“…AR has also been revealed to be able to suppress neurodegeneration in fly models of Huntington's and AD [47]. A recent study with humans aged 45 to 60 years reported an increase in telomerase activity with no discernible change in telomere length in peripheral blood mononuclear cells following AR administration, suggesting that AR can avoid the telomeres erosion, promoting healthy ageing [48]. In aged human participants, AR intake maintained, or even enhanced, the DNA strand break repair, with no toxic effects [49].…”
mentioning
confidence: 99%
“…Salvador et al 50 reported that TA65, a substance extracted from an antiaging medicinal Chinese plant, lengthened telomeres in a randomized, double blind, placebo-controlled study in human subjects aged 53–87 years. Guruprasad et al 51 also reported that amalaki rasayana , a traditional Indian antiaging drug, maintained telomerase activity in human subjects aged 45–60 years. A bioactive extract of C. asiatica , DLBS1649 (25 and 50 µg/mL), also showed an ability in this study to prevent telomere shortening and maintained telomerase activity.…”
Section: Discussionmentioning
confidence: 95%
“…Principal ingredients of Raktda include micronized particles of Kant Lauh Bhasma (Magnetic Iron-Calcined 64 put; VPK) and Mandoor Bhasma (Ferric Oxide-Calcined 64 put; PK) for optimum iron supplementation and absorption and hepatocurative effects [10] , calcium supplementing Praval Pishti (Coral; PK) [11] and Muktashukti Pishti (Pearl Oyster Shell; PK), both of which are better absorbed by the body as compared to conventional mineral based calcium supplements [12] , calcined Varatika Bhasma (Cowrie Shell; V) and Shankh Bhasma (Conch Shell; VPK) for calcium supplementation and aiding in malabsorption and digestive impairments, Shudh Shilajit (Purified Asphaltum; VK) for minerals and micronutrients that improve fatigue induced muscular weakness [13,14] , Giloy Sattva (Guduchi; VPK) for anti-inflammatory [15] , anti-oxidant, hepatoprotective [16,17] , and immuno-stimulatory effects [18,19] , Chuhhara (Dry Dates; VPK) as a rich source of vitamins (e.g. Vit A, B12, and folate) and minerals [20,21] , Amalaki (Indian Gooseberry; VPK) for its cytoprotective and immunomodulatory activity [22,23] , Laung (Clove bud; PK) for its anti-inflammatory and anaesthetic effects [24] , Nagkeshar (Cobra's Saffron Flower; PK) for its antioxidant and anti-arthritic activity [25,26] , Yashtimadhu (Liqourice Root; VP) for anti-inflammatory, antioxidative, immunemodulatory, and hepatoprotective qualities [27] . Raktda also has some ancillary herbs to support the aforementioned active ingredients such as Chhoti Elaichi (Cardamom; VPK), TejPatta (Bay Leaves; VK), Chotti Pippali (Long Pepper; VPK), and Mishri (Cane Sugar).…”
Section: Description Of Raktdamentioning
confidence: 99%